ANALISIS YURIDIS KEDUDUKAN HUKUM LEMBAGA PEMBERI FATWA HALAL DI BEBERAPA NEGARA - Zaka Firma Aditya; Sholahuddin Al-Fatih (Wacana Hukum, 2019)
Consuming halal and safe food products is a constitutional right of citizens. This right is realized through guarantee of halal products, the institution authorized to issue fatwa halla on a product is LPPOM MUI. The results showed that LPPOM MUI issued a halal certificate for a product after previously going through a trial process at the MUI Fatwa Commission. Although judicially the position of MUI is not a state institution, the presence of the MUI, especially LPPOM MUI, can answer the needs of the community. Halal certificates from LPPOM MUI can at least provide legal certainty for the community. Abroad, halal certification institutions are government or private institutions that have their own statutory regulations and standards.